Technology and Ethics in Social Media: A Study of the Phenomenon of Digital Bullying in the Young Generation - Rini, Endah Febri Setiya; Raptis, Paschalis; Sozcu, Omer Faruk; Abdelrhman, Shimaa Ahmed Ahmed Mohamed; Lara-Valenzuela, Cristian (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to examine the prevalence of digital bullying on social media, its psychological and emotional impacts on adolescents, and the correlation between social media use and bullying experiences. This study aims to provide insight into the factors that contribute to digital bullying among adolescents and young people. Methodology: This study used a mixed-methods approach, utilizing questionnaires, structured interviews, and content analysis. The tools used included statistical software for data analysis in the form of descriptive statistics and correlation tests. Five respondents were selected for in-depth interviews. Main Findings: The study found that 80% of respondents engaged in digital bullying, with the most common forms being verbal insults (60%) and hate speech (40%). Frequent social media use (3-5 hours/day) was associated with higher levels of anxiety and loneliness, while the prevalence of bullying was correlated with significant psychological and emotional impacts. Novelty/Originality of this study: This study provides a comprehensive view of digital bullying among adolescents, focusing on its psychological and emotional impacts. It provides new insights into the role of social media use in exacerbating bullying behavior, and suggests interventions such as digital ethics education to reduce its negative impacts.